TECHNOLOGY COMPRESSION FOR REDUCTION VOLUMES TRANSFORMS ON THE BASIS OF CODING THEIR BINARY REPRESENTATION - Юдін, О. К.; Бойко, Ю. П. (Science-based technologies, 2014)
Grounded topicality of the development of information technology and data processing technologies for improving the quality of services. It is shown that the variant of compression technology is to modify the methods of coding bitplanes. Substantiated that the future trend is to transform coding bit descriptions with preliminary identification of a series of binary elements in an adaptive monobasic positional coding. Developed a method of image compression with advanced quantization component transforms discrete cosine transform, which takes into account the embedding conditions adaptive monobasic positional coding. It is proved that in this case provided: raising the compression, with the exception of uncontrolled loss of quality of the reconstructed image due to both psy elimination of redundancy and lack of choice of service data to describe the structural component on the steps of converting the data reduction of processing time as a pre-processing step , and encoding step for reducing the redundancy.